Morphology and structural stability of bismuth-gadolinium co-doped ceria electrolyte nanopowders - Accardo, G.; Spiridigliozzi, L.; Dell'Agli, G.; Yoon, S.P.; Frattini, D. (MDPI Multidisciplinary Digital Publishing Institute, 2019)
The reduction of the sintering temperature of doped ceria ceramics remains an open challenge for their real exploitation as electrolytes for intermediate temperature solid oxide fuel cell (IT-SOFCs) at the industrial level. In this work, we have used Bi (0.5 and 2 mol %) as the sintering aid for Gd (20 mol %)-doped ceria. Nano-sized powders of Bi/Gd co-doped ceria were easily synthesized via a simple and cheap sol-gel combustion synthesis. The obtained powders showed high sinterability and very good electrochemical properties. More importantly, even after prolonged annealing at 700 °C, both of the powders and of the sintered pellets, no trace of structural modifications, phase instabilities, or Bi segregation appeared. Therefore, the use of a small amount of Bi can be taken into account for preparing ceria-based ceramic electrolytes at low sintering temperatures. ？ 2019 by the authors.